The role of parenting styles on effort perseverance: the mediating role of conscientiousness and mindfulness - Ghannad, Simin Zeqeibi; Chegeni, Sahar Ahmadi; Mohammad Ghobadi; Allipour, Sirous (Penerbit Universiti Kebangsaan Malaysia, 2018)
The present study investigates the role of parenting styles on effort perseverance with mediating roles of conscientiousness and mindfulness as moderators. For this purpose, 272 Iranian high school girl students were chosen by stratified random sampling. Data were analyzed by Path Analysis and Hierarchical Regression methods. The results showed that maternal control, parental control and maternal responsibility predict effort perseverance through conscientiousness; and paternal responsibility indicates positive and significant relationship with effort perseverance. Furthermore, findings showed that the relationship between conscientiousness and effort perseverance was moderated by mindfulness. Parenting style is an important factor in predicting effort perseverance through conscientiousness. In addition, being mindfulness has an effective role in relation to conscientiousness and effort perseverance.